Synthesis of indium oxide nanowires encapsulated in amorphous carbon nanostructures on indium tin oxide substrate - Supangat, A.; Bryant, G.; Belcher, W.; Dastoor, P. (Springer Verlag (Germany), 2012)
Indium oxide nanowires encapsulated in amorphous carbon nanostructures have been synthesised on iron coated indium tin oxide substrate via the chemical vapour deposition of acetylene (C2H2). The growth of indium oxide nanowires encapsulated in amorphous carbon nanostructures via solid–liquid–solid mechanism was suggested. The morphology, composition and structure of indium oxide nanowires encapsulated in amorphous carbon nanostructures were characterised by scanning electron microscopy, transmission electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy.